2014
DOI: 10.1039/c4sm00233d
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating and tuning the strain-induced non-linear behavior of polymer nanocomposites: a detailed molecular dynamics simulation study

Abstract: By setting up a coarse-grained model of polymer nanocomposites, we monitored the change in the elastic modulus as a function of the strain, derived from the stress-strain behavior by determining uniaxial tension and simple shear of two typical spatial distribution states (aggregation and dispersion) of nanoparticles (NPs). In both these cases, we observed that the elastic modulus decreases non-linearly with the increase of strain and reaches a low plateau at larger strains. This phenomenon is similar to the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 79 publications
2
31
0
Order By: Relevance
“…[48] A more detailed description of the simulation protocol can be found in our previous publications. [49][50] 3. Results and discussion…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…[48] A more detailed description of the simulation protocol can be found in our previous publications. [49][50] 3. Results and discussion…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…36,37 As the interfacial interaction modes between silica and F-SSBRs followed the order single hydrogen bonds to dual hydrogen/covalent bonds to single covalent bonds, the compounds were ordered as follows with respect to the bound rubber contents: silica/SSBR-g-MPL70 < silica/SSBR-g-MUA70 < silica/SSBR-g-MPTES70, as listed in Table 1. The results indicated that the ller-rubber networks, which were formed through rubber chain bridges anchored onto adjacent llers, [38][39][40] increased gradually with the improving interfacial interactions. Moreover, the bound rubber contents of the silica/SSBR-g-MPTES compounds increased with increasing MPTES contents.…”
Section: Silica/f-ssbr Interfacial Interactionmentioning
confidence: 96%
“…There are usually two kinds of filler networks in a filler‐filled rubber. One is formed by filler‐filler direct contact (filler‐filler contact), and another is formed by polymer chain anchored between neighbor fillers (filler‐rubber network) . Usually, the filler‐filler network is harmful to the dynamic mechanical properties of the sample, while the filler‐rubber network is beneficial to the dynamic mechanical properties of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…One is formed by filler-filler direct contact (fillerfiller contact), and another is formed by polymer chain anchored between neighbor fillers (filler-rubber network). 33,34 Usually, the filler-filler network is harmful to the dynamic mechanical properties of the sample, while the filler-rubber network is beneficial to the dynamic mechanical properties of the sample. RPA measurements could exhibit the filler network in the system, and the interfacial interaction between BCC, silica, and SBR matrix.…”
Section: Resultsmentioning
confidence: 99%